1997
DOI: 10.1074/jbc.272.52.33158
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure Characterization of the Photosystem II D1 and D2 Subunits

Abstract: Mass spectrometry techniques have been applied in a protein mapping strategy to elucidate the majority of the primary structures of the D1 and D2 proteins present in the photosystem II reaction center. Evidence verifying the post-translational processing of the initiating methionine residue and acetylation of the free amino group, similar to those reported for other higher plant species, are presented for the two subunits from pea plants (Pisum sativum L.). Further covalent modifications observed on the D1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…In this context, it is interesting that three clusters of oxidized residues are found in the D1 protein after exposure to light: at the top of helix B (the pheophytin binding domain), at the bottom of helix D (the P680 domain), and at the lumen-exposed C terminus (Sharma et al, 1997). It is possible that oxidation of residues in the last two domains results in conformational changes nearby, rendering them susceptible to cleavage by Deg1 located on the lumenal surface of the thylakoid membrane and resulting in the 5.2-and 16-kD fragments observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is interesting that three clusters of oxidized residues are found in the D1 protein after exposure to light: at the top of helix B (the pheophytin binding domain), at the bottom of helix D (the P680 domain), and at the lumen-exposed C terminus (Sharma et al, 1997). It is possible that oxidation of residues in the last two domains results in conformational changes nearby, rendering them susceptible to cleavage by Deg1 located on the lumenal surface of the thylakoid membrane and resulting in the 5.2-and 16-kD fragments observed here.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that oxidation of residues in the last two domains results in conformational changes nearby, rendering them susceptible to cleavage by Deg1 located on the lumenal surface of the thylakoid membrane and resulting in the 5.2-and 16-kD fragments observed here. Because the D2 protein is less oxidized than D1 (Sharma et al, 1997), it is not surprising that its turnover rate is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Direct experimental evidence for the light-induced oxidation of specific amino acid residues on the D1 and D2 proteins by ROS is lacking. Early studies using electrospray ionization mass spectrometry revealed extensive oxidation of the D1 and D2 proteins in dark-treated PSII reaction centers (18). The use of tandem mass spectrometry recently allowed a more comprehensive identification of oxidized amino acids in PSII (31).…”
Section: Discussionmentioning
confidence: 99%
“…On the PSII electron donor side, a number of natively oxidized residues were identified in the vicinity of the Mn 4 O 5 Ca cluster on the D1, D2, and CP43 subunits (17). On the PSII electron acceptor side, Sharma et al (18) had identified a peptide of the D1 protein ( 130 E-136 R) that lies in the vicinity of Pheo D1 and contained a single oxidative modification on an unidentified residue. Subsequently, Frankel et al (19) identified a number of natively oxidized residues in the vicinity of Q A and Pheo D1 .…”
Section: Significancementioning
confidence: 99%
“…Nevertheless, the N termini of other chloroplast genomeencoded proteins (Michel et al, 1988;Sharma et al, 1997aSharma et al, , 1997bSharma et al, , 1997c, including the large subunit of Rubisco (Houtz et al, 1989), are extensively processed and do not contain an N-formyl group.…”
mentioning
confidence: 99%